Repeatability and divergence among genotypes of Desmanthus sp. in a semiarid region - Cunha, Márcio Vieira da; Santos, Mércia Virginia Ferreira dos; Medeiros, Aurielle Silva; Freire, Joelma de Lira; Debeux Junior, José Carlos Batista; Mello, Alexandre Carneiro Leão de; Lira, Carolina Câmara (Pesquisa Agropecuaria Brasileira, 2021)
The objective of this work was to evaluate the divergence among genotypes of Desmanthus sp. regarding morphological, productive, and qualitative characteristics, as well as to estimate the number of observations necessary to predict the real value of these characteristics. The experiment was conducted in the semiarid of the state of Pernambuco, Brazil, using 26 genotypes of Desmanthus sp. from different locations in the region. Seven evaluations were carried out from July 2013 to July 2014. Tocher’s grouping method and standardized average Euclidean distance were used. The coefficients of repeatability (r) and determination (R2) were estimated using two models of the analysis of variance, principal components based on the correlation or covariance matrix, and structural analysis based on the correlation matrix. The variables with the greatest weights were stem diameter, leaf area index, and forage yield, with frequencies of 22.05, 17.57, and 14.58%, respectively. Morphological, productive, and qualitative variability was observed among the genotypes of Desmanthus sp. All characteristics presented r and R2 of high magnitude in the methods of analysis. Up to four evaluation cycles are required to predict (R2=95%) the real value of stem diameter, peduncle length, plant height, leaf length and width, number of leaves, and pod length.